Cerebral Toxoplasmosis and Latent Tuberculosis Infection in HIV Infected Patient - Rijalun Arridho; Raveinal; Dwitya Elvira (Sumatera Medical Journal, 2024)
Background: Toxoplasmosis is an opportunistic infection caused by Toxopasma gondii, which affects one third of the global human population and commonly involves the central nervous system (CNS)/brain. The diagnosis of obvious sign of imaging method cerebral toxoplasmosis is commonly reported in several case report, but subclinical sign of imaging is uncommon reported. Objective: we reported a case of 28-years-old male with chief complaint headache that worsening since 3 days before admission. Methods: This is a case report. Results: He was first recognized as HIV infected patient on hospital admission. CT scan revealed minimal perifocal oedema in left frontal region. Patient was diagnosed as cerebral toxoplasmosis and latent tuberculosis infection in HIV clinical stadium IV. Patient recieved empirical therapy of cerebral toxoplasmosis and symptom relieved after 7 days of treatment. Cerebral toxoplasmosisis typically associated with HIV infected patient that result in the reactivation of Toxoplasma gondii infection. Conclusions: Clinical presentation of CNS toxoplasmosis varies and normal brain CT can be found despited presumptive diagnosis was revealed.